2015
DOI: 10.1038/mt.2015.1
|View full text |Cite
|
Sign up to set email alerts
|

First-in-man Phase 1 Clinical Trial of Gene Therapy for Advanced Pancreatic Cancer: Safety, Biodistribution, and Preliminary Clinical Findings

Abstract: This phase 1 trial was aimed to determine the safety, pharmacokinetics, and preliminary clinical activity of CYL-02, a nonviral gene therapy product that sensitizes pancreatic cancer cells to chemotherapy. CYL-02 was administrated using endoscopic ultrasound in 22 patients with pancreatic cancer that concomitantly received chemotherapy (gemcitabine). The maximum-tolerated dose (MTD) exceeded the maximal feasible dose of CYL-02 and was not identified. Treatment-related toxicities were mild, without serious adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 26 publications
(31 reference statements)
0
80
0
Order By: Relevance
“…These vectors encode for DCK, a protein (1) we previously demonstrated to sensitize PDAC-derived cells to chemotherapy and to elicit a strong antitumoral bystander effect, 26 and (2) that was recently transferred in patients using nonviral gene therapy during a phase I clinical trial for PDAC. 4 We found that both IDLV and parental vectors drive detectable expression of DCK in PDAC-derived cell lines. When combined with gemcitabine, both vectors inhibited cancer cell proliferation to a similar extent.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…These vectors encode for DCK, a protein (1) we previously demonstrated to sensitize PDAC-derived cells to chemotherapy and to elicit a strong antitumoral bystander effect, 26 and (2) that was recently transferred in patients using nonviral gene therapy during a phase I clinical trial for PDAC. 4 We found that both IDLV and parental vectors drive detectable expression of DCK in PDAC-derived cell lines. When combined with gemcitabine, both vectors inhibited cancer cell proliferation to a similar extent.…”
Section: Discussionmentioning
confidence: 77%
“…During the Thergap clinical trial, we demonstrated that the intratumoral injection of gene therapy is well tolerated, safe, and feasible, and that patients may benefit from the therapy, as 7 out of 9 patients survived more than 1 year after treatment, with 2 long survivors (>2 years). 4 While this clinical trial is important, our next goal is to improve the delivery vehicles used in patients, that is, PEI nonviral vector, to elevate the therapeutic index of gene therapy, to serve in future early phase clinical trials. Our group extensively demonstrated the efficacy of lentiviral-based vectors to transduce and kill PDAC cells both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The different miRNA profiles of 754 miRNA between CAD patients and control subjects were determined using the Life Technologies TaqMan Open Array Human MicroRNA panel 34 . Reverse transcription (RT) and preamplification were performed on all samples using Megaplex Primer Pools miRNA validation.…”
Section: Microrna Expression Profilingmentioning
confidence: 99%